Unusual Presentation of Craniopharyngioma Pituitary Mass in a 71-Year-Old Female: A Case Report - Taylor F. Faust; Punuru Reddy; Jillian Weiss; Michael Steadman; Connie Morizio; Garrett Cail (Case Reports in Endocrinology)
In this report, we present the case of a 71-year-old African-American woman experiencing 2 months of intermittent headaches and episodes of blurred vision. Despite a comprehensive medical history that revealed chronic conditions and previous unrelated surgeries, the initial evaluation appeared to be unremarkable. Following the discovery of a mass on an imaging and a subsequent biopsy, the diagnosis of craniopharyngioma (WHO grade I) was confirmed. However, a brain mass was identified after additional ophthalmologic examination and MRI. This case explores the significance of recognizing atypical presentations of a brain injury that required a specific approach for diagnosis, surgical intervention and treatment, and postoperative care. This case contributes to the constantly evolving understanding of atypical manifestations of tumor characteristics and their complexities, along with the need to develop appropriate patient management strategies and provide optimal outcomes.